Improving Student Learning Outcomes Marketing Strategy Lesson By Applying SFAE Learning Model - Winda Nur Rohmawati; Suwarni Suwarni (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
Research objectives for improving student learning outcomes on the subjects of marketing strategy through the implementation of model learning SFAE. This type of research this is a class action research using a qualitative approach which consists of two cycles with the subject Marketing X grade SMK YPI Darussalam 2 Cerme Gresik Regency. This research consists of four stages: (1) the Planning Act, (2) the implementation of the action, (3) observations (observation), and (4) Reflection. The result of the research shows that cognitive and affective learning outcomes of students have increased significantly.